2019
DOI: 10.3390/ma12132131
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Temperature on the Hydrothermal Synthesis of Hydroxyapatite-Zeolite Using Blast Furnace Slag

Abstract: Blast furnace slag, an industrial by-product, is emerging as a potential raw material to synthesize hydroxyapatite and zeolite. In this study, the effects of temperature on the hydrothermal synthesis of hydroxyapatite-zeolite from blast furnace slag were investigated. Specimens were synthesized at different temperatures (room temperature, 50, 90, 120, or 150 °C). The synthesized specimens were analyzed qualitatively and quantitatively via X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FT-IR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 43 publications
1
19
0
Order By: Relevance
“…This situation occurs because zeolite has a greater surface area and adsorption capacity than HA. Furthermore, Ryu et al [45] confirm previous studies conducted by Kuwahara and co-workers [59,60] who have reported that HA can complement the ability of zeolites that can only absorb cations.…”
Section: Morphology Of Hydroxyapatite-zeolite Compositesupporting
confidence: 76%
See 4 more Smart Citations
“…This situation occurs because zeolite has a greater surface area and adsorption capacity than HA. Furthermore, Ryu et al [45] confirm previous studies conducted by Kuwahara and co-workers [59,60] who have reported that HA can complement the ability of zeolites that can only absorb cations.…”
Section: Morphology Of Hydroxyapatite-zeolite Compositesupporting
confidence: 76%
“…The crystals morphological of the HA-zeolite nano-composite that have been produced by Khorasani et al [47] are mostly cylindrical and elliptical with crystallite sizes between 17-77 nm. It was reported by Ryu et al [45] that HA-zeolite composites synthesized with BFS have a pore size distribution in mesoporous (Fig. 5).…”
Section: Morphology Of Hydroxyapatite-zeolite Compositementioning
confidence: 67%
See 3 more Smart Citations